2008
DOI: 10.1371/journal.pbio.0060254
|View full text |Cite
|
Sign up to set email alerts
|

Brain IGF-1 Receptors Control Mammalian Growth and Lifespan through a Neuroendocrine Mechanism

Abstract: Mutations that decrease insulin-like growth factor (IGF) and growth hormone signaling limit body size and prolong lifespan in mice. In vertebrates, these somatotropic hormones are controlled by the neuroendocrine brain. Hormone-like regulations discovered in nematodes and flies suggest that IGF signals in the nervous system can determine lifespan, but it is unknown whether this applies to higher organisms. Using conditional mutagenesis in the mouse, we show that brain IGF receptors (IGF-1R) efficiently regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
237
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(249 citation statements)
references
References 56 publications
9
237
1
2
Order By: Relevance
“…4 Thus, local synthesis of IGF-I in the brain may be modulated by serum IGF-I input to the brain. Further, as serum IGF-I is elevated in mutant mice lacking IGF-IR in brain (29), and conversely, serum IGF-I is decreased after NP12, brain IGF-I levels may be the result of a balance between local synthesis and serum IGF-I input. In turn, serum IGF-I levels appear to be affected by the amount of serum IGF-I input to the brain.…”
Section: Figure 3 In Vivo Inhibition Of Gsk3 Results In Increased Brmentioning
confidence: 99%
“…4 Thus, local synthesis of IGF-I in the brain may be modulated by serum IGF-I input to the brain. Further, as serum IGF-I is elevated in mutant mice lacking IGF-IR in brain (29), and conversely, serum IGF-I is decreased after NP12, brain IGF-I levels may be the result of a balance between local synthesis and serum IGF-I input. In turn, serum IGF-I levels appear to be affected by the amount of serum IGF-I input to the brain.…”
Section: Figure 3 In Vivo Inhibition Of Gsk3 Results In Increased Brmentioning
confidence: 99%
“…It should be noted that all our studies were measured in tissues isolated from nonstressed mice, and perhaps it is more important to longevity how exactly specific tissues and cells respond to chemical insult. For example, long-lived GHRKO mice (Hauck et al 2002), Ames dwarf ), and female insulin-like growth factor-1 receptor heterozygous (Igf1R +/− ) mice (Holzenberger et al 2003) all showed increased survival following oxidative challenge, relative to WT controls, although this was not seen in long-lived brain-specific Igf1R +/− mice (Kappeler et al 2008). While basal antioxidant activities and oxidative stress is generally unaltered in long-lived Irs1 −/− mice, we suggest that the challenge now is to determine whether IIS mutant mice have enhanced cellular stress resistance, as this will determine whether reduced IIS alone is sufficient to enhance stress resistance.…”
Section: Nsmentioning
confidence: 99%
“…Furthermore, mice with global inactivation of the GHRH receptor (51) or the GH receptor (52) have long lives. Although mice completely lacking the IGF1 receptor have low viability and do not usually survive the postnatal period (53), mice with heterozygous inactivation (w50% reduction) of the IGF1 receptor in total body or the central nervous system including the hypothalamus survive the postnatal period and then have long lives (54,55). An elongation of life span was also observed in mice with reduced local bioavailability of IGF1 (56) and in mice strains with defect IGF1-signalling downstream of the IGF1 receptor (57,58).…”
Section: Mortalitymentioning
confidence: 99%